2019
DOI: 10.1163/2667078x-02002002
|View full text |Cite
|
Sign up to set email alerts
|

Why and How Do Sojourners Talk about Macao? Effects of Perceived Risk and Expected Benefit

Abstract: Due to the growing popularity of digital platforms, social media conversations have been proposed and used as an indicator of public diplomacy outcomes. Despite this, existing research has found that most publics were unwilling to engage with foreign countries on social media. Considering this, this study seeks to identify factors that motivate and/or constrain individuals’ engagement in conversations about foreign countries. A survey and semi-structured interviews were conducted with sojourners who temporaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…When I told my friends about that, they said, 'Shall we go together next time?'" Overall, the findings show that, consistent with the findings from previous studies [59,60], information behaviors of marriage immigrants assisted with the sustainability of the host country in that they selected mostly positive information about the host country to share proactively with friends and family back home. Noticeably, the findings show that recognizing some issues about the destination triggered the informants to talk proactively about life experiences different from those portrayed through media.…”
Section: Self-concept About the Informants' Roles As Information Medi...supporting
confidence: 88%
See 1 more Smart Citation
“…When I told my friends about that, they said, 'Shall we go together next time?'" Overall, the findings show that, consistent with the findings from previous studies [59,60], information behaviors of marriage immigrants assisted with the sustainability of the host country in that they selected mostly positive information about the host country to share proactively with friends and family back home. Noticeably, the findings show that recognizing some issues about the destination triggered the informants to talk proactively about life experiences different from those portrayed through media.…”
Section: Self-concept About the Informants' Roles As Information Medi...supporting
confidence: 88%
“…First, the role of locals as tourism informants has been highlighted from the studies on locals as tourism ambassadors [57] and on the host's roles in the shared economy platforms such as Airbnb [58]. Temporary and permanent immigrants are known to benefit the destination from information behavior perspectives in that they are likely to present positively about the host region [59,60]. Additionally, studies have reported VFR hosts' significant roles as tourism informants during hosting and the guests' expectations of the hosts about having unique and localized information provided [47].…”
Section: Immigrants As Tourism Information Mediatorsmentioning
confidence: 99%
“…Some people may be wary about sharing personal information on social media because of privacy or security concerns and this acts as a behavioral control when it comes to WOM on social media (Ajzen 1991(Ajzen , 2002. It is possible that asking about WOM on social media or tracking social media to assess country image may give us a misleading story about a country's image due to behavioral controls that amount to self-censoring (Choi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this study, we surveyed the GKS students, who are foreigners that had spent at least 10 months in Korea, after which they evaluated the country in a survey. Their evaluations of Korea were more informed due to their direct first-hand and behavioral experiences rather than having obtained mere impressions through symbolic communication (Choi et al 2019;Tam and Kim 2019;Vibber and Kim 2019). In other words, the GKS recipients experienced "close, direct, experiential, and sociological" communication with Koreans during their long stays in the country, compared to other foreigners' "essentially distant, mediated and superficial" communications with Korea and Koreans through the culture media and international news (Yun and Kim 2008, p. 568).…”
Section: Country Imagementioning
confidence: 99%